Prevalence of glutamic acid decarboxylase antibodies amongst young Malaysian diabetics - Nazaimoon, W.M.W.; Faridah, I.; Singaraveloo, M.; Ismail, I.S.; Mohamad, W.B.W.; Letchuman, R.; Rasat, R.; Pendek, R.; Hew, F.L.; Sheriff, I.H.; Khalid, B.A.K. (1999)
This study determined the prevalence of glutamic acid decarboxylase antibodies (GAD Ab) in a group of 926 young Malaysian diabetics of three ethnic groups, Malay, Chinese, and Indian. Patients were clinically diagnosed to be Type 1 or Type 2 before the age of 40 years. The overall GAD Ab positivity was 17.4 (161/926), significantly higher in the Type 1 than the Type 2 diabetics (35.5, 116/329 vs. 7.5, 45/597, P = 0.0001). Compared to GAD Ab negative patients, seropositive diabetics were diagnosed at younger age (21.2 +/- 0.9 vs. 27.4 +/- 0.3 y, P = 0.0001), had lower fasting (289 +/- 27.4 vs. 640 +/- 17.6 pmol/l, P = 0.0001) and post-glucagon C-peptide levels (527 +/- 51.8 vs. 1030 +/- 28.9 pmol/l, P = 0.0001). There were no racial differences in the prevalence of GAD Ab; of the total Type 1, 30.8, 36.4, and 39.4 were Malay, Chinese, and Indian diabetics, respectively and of the total Type 2, 8.8, 8.2, and 4.4 were Malay, Chinese, and Indian diabetics respectively. There was a curvilinear relationship between GAD Ab and the post-glucagon C-peptide levels, suggesting that GAD Ab do play a role in the beta-cells destruction and could be an important immune marker for the LADA group. This study reconfirmed previous reports that the autoimmune mechanisms in the Type 1 Asian diabetics are indeed different from the Caucasians, and further investigations should be carried out to explain the differences. (C) 1999 Elsevier Science Ireland Ltd. All rights reserved.